2023
DOI: 10.1101/2023.01.01.522190
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human brain solute transport quantified by glymphatic MRI-informed biophysics during sleep and sleep deprivation

Abstract: Whether you are reading, running or sleeping, your brain and its fluid environment continuously interacts to distribute nutrients and clear metabolic waste. Yet, the precise mechanisms for solute transport within the human brain have remained hard to quantify using imaging techniques alone. From multi-modal human brain MRI data sets in sleeping and sleep-deprived subjects, we identify and quantify CSF tracer transport parameters using forward and inverse subject-specific computational modelling. Our findings s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 88 publications
2
5
0
Order By: Relevance
“…These velocities are dominated by an osmotic contribution in the intracellular compartment; without it, the estimated fluid velocities drop by a factor of × 34–45. Our estimates are very much in line with the interstitial bulk flow velocities of 5.5–14.5 μm/min [52, 53, 54], 10.5 μm/min [55], or 10.0 μm/min [56], as reported by Nicholson [57], the average interstitial bulk velocities in humans of 1–10 μm/min as quantified by Vinje et al [32], and in the lower range of the 7–50 μm/min bulk flow velocities identified by Ray et al [58]. Comparing with the pioneering modeling study by Asgari et al [37], they report baseline flow estimates resulting from a hydrostatic pressure difference (of unknown origin) alone of ≈1–3 · 10 -2 μm 3 /s.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These velocities are dominated by an osmotic contribution in the intracellular compartment; without it, the estimated fluid velocities drop by a factor of × 34–45. Our estimates are very much in line with the interstitial bulk flow velocities of 5.5–14.5 μm/min [52, 53, 54], 10.5 μm/min [55], or 10.0 μm/min [56], as reported by Nicholson [57], the average interstitial bulk velocities in humans of 1–10 μm/min as quantified by Vinje et al [32], and in the lower range of the 7–50 μm/min bulk flow velocities identified by Ray et al [58]. Comparing with the pioneering modeling study by Asgari et al [37], they report baseline flow estimates resulting from a hydrostatic pressure difference (of unknown origin) alone of ≈1–3 · 10 -2 μm 3 /s.…”
Section: Discussionsupporting
confidence: 90%
“…Nicholson [57], the average interstitial bulk velocities in humans of 1-10 µm/min as quantified by Vinje et al [32], and in the lower range of the 7-50 µm/min bulk flow velocities identified by Ray et al [58]. Comparing with the pioneering modeling study by Asgari et al [37], they report baseline flow estimates resulting from a hydrostatic pressure difference (of unknown origin) alone of ≈1-3 • 10 −2 µm 3 /s.…”
Section: /30mentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless of model choice, we find that about a third of the infused CSF enters the brain from the SAS, as shown in Figure 10. We remark that it was reported in [67] that up to a third of the intrathecal contrast entered the brain.…”
Section: Discussionmentioning
confidence: 67%
“…Another study [35] found a dependence of solute transport on particle size and concluded that transport in the parenchyma is by diffusion alone: however, the basis of this finding has been questioned [28]. More recent studies have provided indirect experimental evidence for flow of ISF in the parenchyma [3638]: these studies present models that show a better fit to tracer data when such a flow is included than when it is not. There is also a theoretical argument for parenchymal flow [18] based on the observed wake/sleep variation in solute clearance [7].…”
Section: Discussionmentioning
confidence: 99%